Bending Effect on Body Wearable Microstrip Patch Antenna - Singh, Jaget (International Journal of Computer Sciences and Engineering, 2019)
A body wearable antenna is supposed to wear on body. It is not possible to keep this antenna in flat condition on different parts of body. It may be subjected to deformation/bending due to movement of body part on which it is mounted. It is expected that the performance of antenna should not change drastically with amount of bending/deformation. So a wearable antenna should also perform efficiently even in bending condition also. In this paper a body wearable antenna has been designed using polycot textile substrate of 3 mm having dielectric constant of 1.48 operating at 2.4 GHz resonant frequency used for ISM band. Bandwidth and S-parameter of antenna having a polycot material (combination of curtain cotton and polyester) as a substrate is measured. Gain and directivity of same antenna has been observed in flat as well as bending condition.